Pembelajaran Daring Ulumul Hadits: Respon Mahasiswa Dan Dampaknya Terhadap Nilai Akhir Semester - Nur Laily Fauziyah (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This study aims to identify the students' response in Ulumul Hadis online learning and its effect toward their achievement. The method used was descriptive qualitative. The research subjects were students at semester four of Islamic Education Department in STIT Al Marhalah Al 'Ulya. The data was obtained from google form questionnaires sent to students who joined Ulumul Hadis class and from interviewing to some students. Data analysis technique used are reduction, data display, and verification. The result is that students' response during having Ulumul Hadis online learning using Whatsapp media is categorized by